2002
DOI: 10.1109/ted.2002.1003754
|View full text |Cite
|
Sign up to set email alerts
|

Third-order intermodulation reduction by harmonic injection in a TWT amplifier

Abstract: A method for reducing the two-tone third-order intermodulation products arising from two carrier frequencies at 1.95 and 2.00 GHz is demonstrated in a traveling wave tube-distributed amplifier. The optimum amplitude and phase of an injected second harmonic and the resulting intermodulation suppression of up to 24.2 dB are examined for fundamental drive levels approaching saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…For 3IM injection, the 3IM at 2.00 GHz is generated by mixing the harmonic and the fundamental . The frequency doubler is capable of doubling input frequencies from 1.5-5 GHz and avoids any phase drifts between the fundamental and second harmonic or 3IM frequencies thus resulting in higher suppression than reported in [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 3IM injection, the 3IM at 2.00 GHz is generated by mixing the harmonic and the fundamental . The frequency doubler is capable of doubling input frequencies from 1.5-5 GHz and avoids any phase drifts between the fundamental and second harmonic or 3IM frequencies thus resulting in higher suppression than reported in [20].…”
Section: Methodsmentioning
confidence: 99%
“…Suppression of third-order intermodulation or 3IM ( , ) products by harmonic injection in TWTs was first investigated by Sauseng et al [19] who observed a 6-7 dB reduction in the upper and lower 3IMs ( and , respectively, assuming ) at saturation. More recently, 3IM suppression of up to 24 dB has been reported by our group [20]. Second-harmonic injection to control 3IM has also been studied analytically [17] and numerically [14], [17].…”
Section: Introductionmentioning
confidence: 94%
“…The S-MUSE model (25)- (29) may be written in the following vector form that is particularly useful for analysis: (30) where is a 5 2 -dimensional complex vector, is a complex matrix, is a complex 3-tensor, and overdot represents . The detailed specification and indexing of , , and as well as a formula to compute the components of are found in Appendix II.…”
Section: ) Vector Formmentioning
confidence: 99%
“…Under suitable conditions, the S-MUSE model in the vector form (30) can be solved with a series solution where each vector satisfies a differential equation that is a linear system forced by quadratic terms formed by combinations of with . For example, the drive frequencies are in and they combine quadratically to force the differential equation for so as to cause second harmonics in .…”
Section: Analysis Using S-musementioning
confidence: 99%
“…It has been suggested to employ feed forward linearization technique in link to enhance the system performance [1]. There are different methods of linearization [2][3][4][5] but feed forward linearization methods gives better results than all. The feed forward technique is better because it gives a large improvement in IMD3 reduction.. An analysis of 16×10 Gbps WDM system was carried out in [6][7] using the feedforward linearization scheme proposed in [1].…”
Section: Introductionmentioning
confidence: 99%